Development of Indoor Air Quality Measuring Device and Application to Support Campus in Post-Covid-19 Pandemic Class Preparation - Hendra Jatnika; Mochamad Farid Rifai; Yudhi S. Purwanto (International Journal of Social Service and Research, 2023)
The Covid-19 pandemic has left our campus classrooms empty for a long time. The main concern of this research is to ensure the cleanliness of the classroom, not only for the materials and the room, but also for the air in it. Clean and safe indoor air is determined by several factors, one of which is air ventilation. Standard classrooms usually need to have plenty of ventilation to ensure airflow, but in general, in most large cities, the case is not that simple. Some schools have a narrow area, some are in dense rural areas or in industrial areas, some use air conditioning but lack maintenance, etc. This research focuses on the development of indoor air quality measuring device that can be used to check the air quality of classrooms and transmit the results to parents and other related parties. The device is made using a wi-fi integrated microcontroller module which is equipped with sensors measuring air conditions. It is also connected to the application on the android phone, and the data is stored on the web. It is also embedded with geolocation tagging to indicate the exact location of activity. The stored data can be used as basic data to make predictions about air quality conditions in a particular place in the future.